STRATEGI PENGEMBANGAN POTENSI ALAM BANJAR PAKRAMAN SIDEMBUNUT KELURAHAN CEMPAGA SEBAGAI DAYA TARIK WISATA UNGGULAN KABUPATEN BANGLI - Widiantara, I G A Bagus; Suarsana Ariesta, I Putu Agus (Jurnal Manajemen Pelayanan Hotel, 2021)
In general, tourism potential is divided into two groups, namely: cultural potential and natural potential. Tourism potential is everything in an area / tourist spot that can be developed into a tourist attraction so that it can become an attraction for tourists to visit the area. Banjar Pakraman Sidembunut has many tourist attractions, including natural, spiritual, culinary, cultural and historical attractions, which are centered in the catus patha or pempatan agung area. This area also has a village temple with kori agung with unique Balinese architecture since the 8th century. The community establishes a shelter around this catus patha by utilizing the natural potential that has existed for a long time. Ecotourism Bukit Cemeng is one of them, which is located at the eastern end of Bukit Bangli, the western boundary is at Banjar Brahmana Bukit and the eastern boundary is in Sidembunut with many potentials, among others Pancuran Suji Tourism is two pancoran locations where one is used for a holy place to do melukat while the other is a public bath, Hyang Ukir Temple which is worthy of being a spiritual location and starting trekking towards the Bukit Cemeng ecotourism, there is also Taman Sari River which is a public bath and irrigation route for rice fields, and in Taman Sari there is also an artificial cave, Gua Merku, besides that there is also a small industry of making souvenirs from solid stone chisels, wood and woven bamboo. So that with this great potential, Bukit Cemeng Ecotourism can develop into a leading tourist attraction in Bangli Regency. Keywords: tourism potential, tourist attraction, ecotourism